Guru Dalam Peningkatan Profesionalisme, Agen Perubahan Dan Revolusi Industri 4.0 - I Made Sedana (Jurnal Penjaminan Mutu, 2019)
The progress of science and technology in the era of globalization which has now led to the era of industrial revolution 4.0 brings the effect of extraordinary changes to the pattern of life of humanity in this hemisphere. Teachers as educators are implementers of the education profession, in carrying out their professions there are several requirements that must be met by a teacher in order to have qualifications and credibility in the field of education. This is a condition for the realization of professional teachers, namely having overall competency both in the field of education and learning methodology as well as the substance of the scientific field. Teachers will become a developing profession when constantly changing themselves, because practical education will continue in different situations and times. Improving the ability of teachers to carry out their profession should not be passive but must be proactive, do not wait for opportunities but seek opportunities